1981
DOI: 10.1007/bf00018366
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the biomass of freshwater mussels (Bivalvia: Unionidae) from shell dimensions

Abstract: We have compared the convenience and accuracy of two models using 6 shell dimensions for predicting 4 biomass parameters for 4 species of southern U.S.A. unionids (Quadrula quadrula, Q. pustulosa, Lampsilis anodontoides, and Amblemaperplicata).Prediction of whole wet weight, tissue wet weight, tissue dry weight, and shell dry weight as a linear function of (shell length)3 was accurate, even with extremely small sample sizes. In addition, this method is very convenient for field use because it requires one simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Scaling exponents below 2.5 are unusual in bivalves. Golightly & Kosinski (1981) suggested that biomass scaled as the cube of the length in bivalves. Powell & Stanton (1985) reviewed a range of molluscan taxa, gastropod and bivalve, and found that the scaling exponent did not differ substantively from the value of 3 earlier recommended by Golightly & Kosinski (1981).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling exponents below 2.5 are unusual in bivalves. Golightly & Kosinski (1981) suggested that biomass scaled as the cube of the length in bivalves. Powell & Stanton (1985) reviewed a range of molluscan taxa, gastropod and bivalve, and found that the scaling exponent did not differ substantively from the value of 3 earlier recommended by Golightly & Kosinski (1981).…”
Section: Discussionmentioning
confidence: 99%
“…Golightly & Kosinski (1981) suggested that biomass scaled as the cube of the length in bivalves. Powell & Stanton (1985) reviewed a range of molluscan taxa, gastropod and bivalve, and found that the scaling exponent did not differ substantively from the value of 3 earlier recommended by Golightly & Kosinski (1981). Perusal of a haphazardly gathered selection of reports of allometric relationships, not intended by any means to be a thorough review, reveals that values between 2.5 and 3 are commonplace and that values below 2.5 are exceedingly rare (Table 3, Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…Their unselective feeding and high filtering rates affect phytopiankton populations (Winter, 1978;Price & Schiebe, 1978;Tessier et al, 1984) and stimulate microinvertebrate production (Sephton, Paterson & Fernando, 1980). They can make up much of the benthos biomass in lakes (Magnin & Stanczykowska, 1971;Golightly & Kosinsky, 1981), their juveniles are important food for fish (Negus, 1966) and smaU mammals (Coker ei al., 1922;Cvancara, 1970), and their glochidia can be fatal parasites of fishes (Lefevre & Curtis, 1910;Matteson, 1948). Freshwater mussels also have an expanding role in applied ecological research.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater mussels may have a major impact on phytoplankton dynamics and lake management because their feeding is unselective (Winter 1978;Tessier et al 1984) and filtering rates are high (Price and Schiebe 1978). Mussels can make up much of the benthos biomass in lakes (Magnin and Stanczykowska 1971;Golightly and Kosinsky 1981), affect alkalinity budgets (Green 1980), and stimulate microinverte-brate production (Sephton et al 1980). They are of paleontological (Green 1972) and archaeological (Kunz 1893;Hill 1983) interest.…”
mentioning
confidence: 99%